Small NRPS-like enzymes in Aspergillus sections Flavi and Circumdati selectively form substituted pyrazinone metabolites - Lebar, Matthew D.; Mack, Brian M.; Carter-Wientjes, Carol H.; Wei, Qijian; Mattison, Christopher P.; Cary, Jeffrey W. (Frontiers in Fungal Biology, 2022)
Aspergillus fungi produce mycotoxins that are detrimental to human and animal health. Two sections of aspergilli are of particular importance to cereal food crops such as corn and barley. Aspergillus section Flavi species like A. flavus and A. parasiticus produce aflatoxins, while section Circumdati species like A. ochraceus and A. sclerotiorum produce ochratoxin A. Mitigating these toxins in food and feed is a critical and ongoing worldwide effort. We have previously investigated biosynthetic gene clusters in Aspergillus flavus that are linked to fungal virulence in corn. We found that one such cluster, asa, is responsible for the production of aspergillic acid, an iron-binding, hydroxamic acid-containing pyrazinone metabolite. Furthermore, we found that the asa gene cluster is present in many other aflatoxin- and ochratoxin-producing aspergilli. The core gene in the asa cluster encodes the small nonribosomal peptide synthetase-like (NRPS-like) protein AsaC. We have swapped the asaC ortholog from A. sclerotiorum into A. flavus, replacing its native copy, and have also cloned both asaC orthologs into Saccharomyces cerevisiae. We show that AsaC orthologs in section Flavi and section Circumdati, while only containing adenylation-thiolation-reductase (ATR) domains, can selectively biosynthesize distinct pyrazinone natural products: deoxyaspergillic acid and flavacol, respectively. Because pyrazinone natural products and the gene clusters responsible for their production are implicated in a variety of important microbe-host interactions, uncovering the function and selectivity of the enzymes involved could lead to strategies that ultimately benefit human health.